KOMPRES HANGAT BERPENGARUH TERHADAP NYERI PERSALINAN KALA I FASE AKTIF PADA IBU BERSALIN - Effendy, Dhea Alaeyda; Utami, Vida Wira; Maternity, Dainty; Sunarsih, Sunarsih (Universitas Malahayati Bandar Lampung, 2021)
Background In Indonesia in 2008 there were 373,000,000 pregnant women, and 107,000,000 (28.7%) experienced anxiety in the face of childbirth. Another study stated that pregnant women in facing labor experienced severe anxiety as much as 47.7%, moderate anxiety as much as 16.9% and mild anxiety as much as 35.4%. Some non-pharmacological techniques that can increase comfort in dealing with the labor process are relaxation and guided imagination, distraction, music, cutaneous stimulation which includes massage, deepback massage,warm/cold compresses, herbal tens.The purpose of this study is to know the effect of warm compresses on labor pain in the active phase of the first stage of childbirth in BPM Melita Sari, S.ST, North Sungkai District, North Lampung Regency in 2021. Methods This type of research is quantitative, the research design uses an experiment with a one group pretest-posttest design approach. The population and sample in this study were mothers who gave birth at BPM Melita Sari, S.St. North Sungkai District, North Lampung Regency with an average monthly visit of 32 mothers who gave birth. Purposive sampling technique, research using univariate analysis and bivariate independent t-test. Result The average active phase I pain in childbirth who was given the warm compress technique with a mean pretest value of 8.33 and a mean post-test of 6.33, which means that the active phase I labor pain in childbirth experienced a decrease. The average pain that was not given a warm compress technique with a mean pretest value of 8.73 and a mean post-test of 8.27, which means that the active phase I labor pain in labor experienced a decrease but was not significant and remained constant in the severe pain category. The difference in labor pain in the first stage of the active phase in maternity mothers who were given warm compresses and the control group, by looking at the mean pretest value of warm compresses of 8.33 and the mean of 8.73 in the control group.Conclusion the mean post-test for the warm compress group was 6.33 and the mean for the control group was 8.27. p-value = 0.000 <0.05 which means that there is an effect of warm compresses on labor pain in the first stage of the active phase in mothers giving birth at BPM Melita Sari, S.ST, North Sungkai District, North Lampung Regency in 2021.Suggestion input for clients in order to know how to divert pain, pain can be eliminated without having to use medical drugs (Pharmacology) pain can be reduced by several kinds of complementary therapies such as warm compresses. Keywords : Warm Compress, Labor Pain, Stage I Active Phase ABSTRAK Latar Belakang di Indonesia pada tahun 2008 terdapat 373.000.000 ibu hamil, dan yang mengalami kecemasan dalam menghadapi proses persalinan ada sebanyak 107.000.000 (28,7%). Penelitian lain menyebutkan bahwa ibu hamil dalam menghadapi persalinan mengalami kecemasan berat sebanyak 47,7%, kecemasan sedang sebanyak 16,9% dan kecemasan ringan sebanyak 35,4%. Beberapa teknik non farmakologi yang dapat meningkatkan kenyamanan dalam menghadapi proses persalinan yakni relaksasi dan imajinasi terpimpin, distraksi , musik, stimulasi kutaneus yang meliputi, masase, deepback massage, kompres hangat/ dingin, tens herbal.Tujuan penlitian ini diketahui pengaruh kompres hangat terhadap nyeri persalinan kala I fase aktif pada ibu bersalin di BPM Melita Sari, S.ST Kecamatan Sungkai Utara Kabupaten Lampung Utara Tahun 2021. Metode Jenis penelitian kuantitatif, desain penelitian menggunkan eksperimen dengan pendekatan pretes postes with control group design, Populasi dan sampel dalam penelitian ini adalah ibu bersalin di BPM Melita Sari, S.St Kecamatan Sungkai Utara Kabupaten Lampung Utara dengan rata-rata kunjungan perbulan sebanyak 32 ibu bersalin., teknik sampling purposive sampling, penelitian menggunakan analisa univariat dan bivariat t-tesindepdnen. Hasil Rata-rata nyeri kala I fase aktif pada ibu bersalin yang diberi teknik kompres hangat dengan nilai mean pretes 8,33 dan mean postes 6,33 yang artinya nyeri persalinan kala I fase aktif pada ibu bersalin mengalami penurunan. Rata-rata nyeri yang tidak diberi teknik kompres hangat dengan nilai mean pretes 8,73 dan mean postes 8,27 yang artinya nyeri persalinan kala I fase aktif pada ibu bersalin mengalami penurunan akan tetapi tidak signifikan dan tetap konstan pada kategori nyeri berat. Perbedaan nyeri persalinan pada kala I fase aktif pada ibu bersalin yang diberi kompres hangat dan kelompok kontrol, dengan melihat nilai mean pretes kompres hangat sebesar 8,33 dan mean pada kelompok kontrol 8,73.Kesimpulan mean postes kelompok kompres hangat sebesar 6,33 dan mean pada kelompok kontrol 8,27. p-value = 0.000<0.05 yang artinya terdapat pengaruh kompres hangat terhadap nyeri persalinan pada kala I fase aktif pada ibu bersalin di BPM Melita Sari, S.ST Kecamatan Sungkai Utara Kabupaten Lampung Utara Tahun 2021.Saran masukan bagi klien agar dapat mengetahui bagaimana cara mengalihkan nyeri, nyeri dapat dihilangkan tanpa harus menggunakan obat secara medis (Farmakologi) nyeri dapat dikurangi dengan beberapa macam terapi komplementer seperti kompres hangat. Kata Kunci : Kompres Hangat, Nyeri Persalinan, Kala I ase Aktif